Natural course of postoperative C-reactive protein and erythrocyte sedimentation rate in unilateral and simultaneous bilateral total knee arthroplasty - Mustafa Alper Incesoy; Cemil Burak Demirkiran; Hakan Batuhan Kaya; Muhammed Ali Geckalan; Aysegul Yabaci Tak; Nurzat Elmali; Fatih Yildiz; Gokcer Uzer (BMC Musculoskeletal Disorders)
Abstract Background C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) are valuable markers for detecting periprosthetic joint infection (PJI) post-total knee arthroplasty (TKA). However, their prolonged elevation after TKA diminishes diagnostic reliability. This study investigates CRP and ESR trends in unilateral (U-TKA) and simultaneous bilateral TKA (SB-TKA) patients, comparing their patterns. Methods Between 2017 and 2023, preoperative and postoperative (weeks 2, 4, 6) CRP and ESR levels were assessed in U-TKA (32 patients) and SB-TKA (29 patients) groups for gonarthrosis. Results Median preoperative CRP levels were 1.13 mg/dL (U-TKA) and 0.2 mg/dL (SB-TKA), with corresponding ESR levels of 13.50 mm/h and 10 mm/h. While CRP and ESR increased more in SB-TKA, differences were statistically insignificant (p > 0.05). Both groups showed significant differences in CRP and ESR values at all time points (p < 0.05). U-TKA patients reached CRP < 5 mg/dL and ESR < 30 mm/h by the 6th postoperative week. SB-TKA patients did not exhibit significantly higher CRP and ESR levels at various intervals compared to U-TKA patients (p > 0.05). Conclusion This study delineates postoperative CRP and ESR trends in U-TKA and SB-TKA for osteoarthritis. CRP values decreased below 5 mg/dL, and ESR values below 30 mm/h within 6 weeks in both groups. Statistically significant differences in CRP and ESR values were observed at all time points. No significant differences were found in CRP and ESR trends between both groups. These findings aid physicians in interpreting laboratory reports for PJI determination. Level of Evidence: III.